Microstructural characterization and enhanced hardness of nanostructured Ni3Ti– NiTi (B2) intermetallic alloy produced by mechanical alloying and fast microwave-assisted sintering process. (April 2021) - Akbarpour, M.R.; Alipour, S.; Najafi, M.; Ebadzadeh, T.; Kim, H.S.
Abstract: In this paper, the rapid synthesis of nanostructured NiTi–Ni3 Ti intermetallic alloy from titanium and nickel powders through mechanical alloying followed by microwave-assisted sintering process was investigated. The sintered samples at different temperatures exhibited major phases of NiTi– B2 and Ni3 Ti, and minor phases of NiTi–B19′ and Ti2 Ni. The density, porosity and microhardness of the sample varied based on the sintering temperature, in which the highest density and microhardness (~750 H V) were obtained at sintering temperature of 1100 °C. Based on the results of this research, the microwave-assisted sintering can be applied to fabricate Ni–Ti alloys with improved mechanical properties for biomedical applications. Highlights: Ni-50 mol. % Ti alloy was successfully sintered via 15 min microwave-assisted heating. HRTEM analysis revealed major phases of NiTi– B2) and Ni3Ti in the alloy structure. The highest microhardness of 750 H V was indicated for the sample sintered at 1100 °C. The high hardness was attributed to the nanostructuring and Ni3Ti phase formation.